Dreams from my father a story of race and inheritance - Obama, Barack; Bronstein, Jacob; Smith, Brian (New York : Random House Audio, 2005)
In New York ... Barack Obama learns that his father--a figure he knows more as a myth than as a man--has been killed in a car accident. This sudden death inspires an emotional odyssey--first to a small town in Kansas, from which he retraces the migration of his mother's family to Hawaii, and then to Kenya, where he meets the African side of his family, confronts the bitter truth of his father's life, and at last reconciles his divided inheritance
Title from container
Keywords: Obama, Barack; African Americans -- Biography; Racially mixed people -- United States -- Biography; Racism -- United States; United States -- Race relations